2010
DOI: 10.1159/000321607
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Critical Period for Neocortical Neurogenesis after Pediatric Brain Injury

Abstract: Pediatric traumatic brain injury (TBI) is a significant and underappreciated societal problem. Whereas many TBI studies have evaluated the mechanisms of cell death after TBI, fewer studies have evaluated the extent to which regeneration is occurring. Here we used a cryoinjury model to damage the somatosensory cortex of rats at postnatal day 6 (P6), P10 and P21. We evaluated the production of new neocortical neurons using a combination of 5-bromo-2-deoxyuridine (BrdU) labeling combined with staining for doublec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 67 publications
5
33
1
Order By: Relevance
“…77 Several TBI studies using a cortical impact injury model in mice and rats have demonstrated new neurons near the focal site of injury from 3 days to 3 weeks postinjury. 7,66,70 Indeed, Covey et al 13 showed that the critical period for neocortical neurogenesis in postnatal Day 6 mice was between 4 and 7 days after cryoinjury. Our studies in the 7-dayold (infant) piglet revealed, 7 days after injury, a modest increase in migrating neuroblasts in the white matter of the hemisphere injured via cortical impact.…”
Section: Discussionmentioning
confidence: 99%
“…77 Several TBI studies using a cortical impact injury model in mice and rats have demonstrated new neurons near the focal site of injury from 3 days to 3 weeks postinjury. 7,66,70 Indeed, Covey et al 13 showed that the critical period for neocortical neurogenesis in postnatal Day 6 mice was between 4 and 7 days after cryoinjury. Our studies in the 7-dayold (infant) piglet revealed, 7 days after injury, a modest increase in migrating neuroblasts in the white matter of the hemisphere injured via cortical impact.…”
Section: Discussionmentioning
confidence: 99%
“…While neurogenesis peaks during gestational periods, by adulthood the generation of neurons is restricted to the dentate gyrus (DG) of the hippocampus and the lateral wall of the subventricular zone (SVZ) [64,67].…”
Section: Age-at-injury Response To Preclinical Tbimentioning
confidence: 99%
“…No comparisons to adult CCI injury were made. Unfortunately, data regarding age effects on neurogenesis are still lacking since numerous studies in mice or rats either have not performed adult comparisons [72] or have not used relevant TBI models [67,73]. Of note, while naïve P9 mice display increased proliferation in the DG compared to P21, hypoxic-ischemic injury adversely affected neurogenesis in P9 but greatly enhanced it in P21 suggesting that early adolescence may display a critical window of regenerative potential that may be lost in adulthood.…”
Section: Age-at-injury Response To Preclinical Tbimentioning
confidence: 99%
“…Immunofluorescence was performed on the 40-μm-thick frozen sections as previously described [19] and the sections were counterstained with 1 μg/ml DAPI for 5-10 min. The slides were coverslipped with Fluoro-Gel.…”
Section: Brdu Immunofluorescencementioning
confidence: 99%